The interdisciplinary profile of theology—fashion or necessity? - Anderwald, Andrzej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
This review pertains to the book Evolutionary Theology (Teologia ewolucyjna) written by Wojciech P. Grygiel and Damian Wąsek. The book presents a distinct and modern viewpoint on theology by offering a comprehensive analysis of the characteristics of theological language and utilizing it to reevaluate certain theological beliefs, such as the concept of original sin, within the framework of the ever-changing understanding of the Universe. This approach contributes significantly to the restoration of theology’s credibility in modern culture by bridging the gap between science and theology.